2022
DOI: 10.1177/03611981221117542
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Ride-Hailing Driver Attrition and Supply in the City of Chicago Through the COVID-19 Pandemic

Abstract: The flexible nature of on-demand ride services provided by transportation network companies (TNC) has resulted in unique supply-side challenges as the industry deals with the COVID-19 pandemic. Early during the pandemic, there was a 70% decrease in the number of drivers accepting trips on TNC platforms, as individual drivers chose to reduce their risk of viral infection and abide by social distancing recommendations. Given the two-sided market nature of TNCs, the decrease was also the effect of reduced rider d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The phobia of pandemic is continuing, which has created panic among ride-hailing users, thus adversely affecting ride-hailing customers. In absence of the research on ride-hailing, our findings are consistent with the findings of Hegde et al . (2022) and Fielbaum et al .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The phobia of pandemic is continuing, which has created panic among ride-hailing users, thus adversely affecting ride-hailing customers. In absence of the research on ride-hailing, our findings are consistent with the findings of Hegde et al . (2022) and Fielbaum et al .…”
Section: Discussionsupporting
confidence: 93%
“…The coronavirus-related misleading information, its transmission and its consequences have been documented by Freiling et al (2023) and preventive actions were suggested by Seetharaman (2020). The availability of a vast amount of inaccurate information (knowingly or unknowingly) on social media resulted in panic among ride-hailing users (Fielbaum et al, 2023;Hegde et al, 2022). In the absence of literature on the effect of infodemic on the intention to ride-hailing, we take the support of anecdotal evidence that the consumers keep away from these services based on the hearsay that they may be infected with the virus and it may be life-threatening.…”
Section: Theoretical Background Proposed Research Model and Hypothese...mentioning
confidence: 99%
See 1 more Smart Citation